Activation of selected body muscles analysis during cycling, training rollers and ergometer use-a case study - Škopek, M.; Marešová, M. (Journal of Outdoor Activities, 2018)
Introduction: This article describes research of muscle activation during cycling, ergometer and training rollers cycling. Aim of Study: The main objective of the study is to find out coordination similarities or differences between muscle activation of the observed muscles during three types of cycling in use, this may help us understand which type of cycling simulation is better and approximating to real cycling conditions. This study is a pilot project on which other research will build in the future. Material and Methods: The results were gained based on a comparative analysis of electromyography signals of muscle activation combined with the overall kinetic analysis via synchronized video recording of one proband. The main model for muscle activation was established to be the measurement of muscle activation while cycling on a road bike in the natural environment. Base on this model the research part of the work can be then regarded as a case study, in which the main goal is to observe the sequencing of muscle activation. Results: The results show that training rollers provide a better simulation of natural conditions in terms of muscle activation. Conclusion: Therefore, training rollers are a good and appropriate method for cycling training practice for sportsmen.